Optimalisasi Zakat Produktif Pada Peningkatan Usaha Mikro Mustahik (Studi Kasus Pada Program Purbalingga Sejahtera BAZNAS Kabupaten Purbalingga) - Oktia Ningsih; Ramini Hadi (Profesional Muda Cendekia Publishing, 2022)
The problem of poverty that still exists today cannot be separated from the low economic income of the community. One of the causes of poverty in Indonesia is that the poor have difficulty raising capital. Zakat can be relied upon as a mechanism to overcome this problem, of course changing the distribution system which is generally consumptive in nature to be productive or in other words zakat is not only used once but has other impacts for development. The purpose of this study was to determine the optimization of productive zakat on increasing mustahik micro businesses in the Purbalingga Sejahtera Program at BAZNAS Purbalingga Regency. The type of research used is field research or direct research conducted in the field or on informants. This research was conducted using a qualitative method with a descriptive approach. After conducting research and analysis, it can be concluded that the optimization of productive zakat in increasing mustahik micro businesses in the Purbalingga Sejahtera Program implemented by BAZNAS Purbalingga Regency is not optimal. This is because, every indicator to assess the optimization of a program is correct and correct. Furthermore, to further optimize the Purbalingga Sejahtera Program, namely productive zakat funds in achieving program goals, BAZNAS Purbalingga Regency is to be able to improve again in terms of assistance to mustahik as a whole. The limited number of amil, it is recommended to open volunteers from students of zakat and waqf management study programs.